Impact of the surface functionalization on nanodiamond biocompatibility: a comprehensive view on human blood immune cells. (30th April 2020) - Fusco, Laura; Avitabile, Elisabetta; Armuzza, Valentina; Orecchioni, Marco; Istif, Akcan; Bedognetti, Davide; Da Ros, Tatiana; Delogu, Lucia Gemma
Abstract: Nanodiamonds (NDs) represent a class of carbon nanostructures widely investigated as promising biomedical nanotools. The possible immune system reactions indicate success or failure for any nanosystem bioapplication. Moreover the assessment of the role of nanomaterial functionalization on the immune system response needs to be fully elucidated. We aimed to dissect the immunologic impact of two NDs differing for their functionalization, carboxylic acid modified NDs (NDs-COOH) and amino-functionalized NDs (NDs-NH2 ), presenting a glycolic chain as spacer. We used human peripheral blood mononuclear cells (PBMCs) as model for potential biomedical scenario of NDs interaction with the human body. The ND immunologic effects were depicted toward the complex mix of PBMCs. The results showed that both functionalizations possess high hemocompatibility but NDs-COOH induced a cell viability reduction, affecting monocytes. The ND impact was depicted through immune activation markers, immune-response gene expression and cytokine secretion analysis. Immune markers confirmed the impact on monocytes, more evident for NDs-COOH. Both NDs affected the immune response, however NDs-COOH showed more prominent responses, evoking pronounced regulation of immune-modulatory transcripts. The cytokine analysis confirmed gene expression data for proinflammatory cytokines related to the innate response. Our findings reveal that NDs decoration with an amino-terminating chain enhances their immunologic compatibility. Graphical abstract: Image 1